Synthesis of one-component type II dithioxanthone-disulfide photoinitiator and investigation of photophysical and photochemical properties - Koyuncu, Umut; Metin, Eyup; Ocal, Nuket; Arsu, Nergis (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Herein, we report the successful synthesis of dithioxanthone-disulfide [TX-S-](2) as a new one-component type II photoinitiator. Photophysical properties of [TX-S-](2) in terms of fluorescence and phosphorescence properties were investigated and low fluorescence quantum yield was observed, which indicates an efficient intersystem crossing (ISC) that leads to the generation of triplet states. Efficiently produced initiating thiyl radicals from the triplet states lead to polymerization of methyl methacrylate with [TX-S-](2) in air atmosphere. To elucidate the initiating mechanism, a disulfide exchange reaction was performed in the presence of diphenyl disulfide [Ph-S-](2), and the obtained results from HQ-TOF confirmed that [TX-S-](2) disulfide bond cleavage occurs upon irradiation with light. Initiating mechanism of [TX-S-](2) revealed the potential usage of this compound as a self-healing agent due to the efficient cleavage of disulfide bonds. In conjunction with the experimental studies series of Density Functional Theory calculations were performed and various photophysical and photochemical properties, including HOMO and LUMO, were computationally calculated and visualized.
Keywords: Self-healing; Disulfide; Photochemical; Photophysical; Photoinitiator; Synthesis; Polymer Science